PENGEMBANGAN HANDOUT MATERI PROTISTA KELAS X BERBASIS KEARIFAN PANGAN LOKAL “UTA METI” MASYARAKAT AMBON, INDONESIA - Janed Lauren Soplantila; Jendri Mamangkey; Marina Silalahi (Bio-Lectura : Jurnal Pendidikan Biologi, 2023)
The development of teaching materials in Indonesia is still minimal, especially teaching materials based on local wisdom in the form of customs, traditions and food. Even though it combines elements of local wisdom in a lesson such as science learning. Uta meti is one of the local wisdoms of the Ambon area, especially Latuhalat village which is quite well known and on average the local people have consumed it. Interestingly uta meti is a type of algae belonging to the kingdom Protista, which can be developed into an alternative teaching material. This study aims to develop an alternative teaching material in the form of handout based on local wisdom related to protist material for class X SMA to make it easier for students to understand protist material. This type of research is R&D research with the ADDIE model, the test subjects in this development research are 6 experts to validate the product and 34 class X students of SMAN 10 Ambon as potential users. Data collection techniques were carried out by interviews and questionnaires. Data were analyzed descriptively quantitatively and qualitatively, using a likert scale as a measurement scale. The results showed that in the validation test and 2 field trials the uta meti local food wisdom- based protista handout developed for class X students was included in the very feasible category with an average percentage of 2 trials of 81% and 83%.